PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Susanti Rimadhana, 12.05.52.0167; Badjuri, Achmad (Students Journal of Accounting and Banking, 2016)
This study aimed to examine the effect of company size, company profiles, profitability, board size, managerial ownership, operating efficiency ratio and independent directors on the disclosure of corporate social responsibility in the LQ-45 company listed on the Indonesian Stock Exchange. The population in this study are all companies listed on the Indonesian Stock Exchange (BEI) during the period 2013-2015. Samples were selected using purposive sampling method LQ-45 as many as 15 companies.mechanical testing data is by using multiple linear regression. The analysis showed that the variables that have a significant influence on the disclosure of corporate social responsibility is a company size, profitability, board size, managerial ownership, operating efficiency ratio. While the company profile and independent commissioners had no significant effect on the disclosure of corporate social responsibility.Â Keywords:Â Characteristics of The Enterprise, Corporate Social Responsibility